2009
DOI: 10.1080/07420520902924939
|View full text |Cite
|
Sign up to set email alerts
|

Clock Genes Display Rhythmic Expression in Human Hearts

Abstract: Thus far, clock genes in the heart have been described only in rodents, and alterations of these genes have been associated with various myocardial malfunctions. In this study, we analyzed the expression of clock genes in human hearts. Left papillary muscles of 16 patients with coronary heart disease, 39 subjects with cardiomyopathy, and 9 healthy donors (52 males and 12 females, mean age 55.7+/-11.2; 16-70 yrs) were obtained during orthotopic heart transplantation. We assessed the mRNA levels of PER1, PER2, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 43 publications
5
63
1
Order By: Relevance
“…By periodic sinusoidal regression analysis, they observed that peak infarct size was 82% greater than trough and occurred at 1:00 am onset of ischemia, a time at which the cardiomyocyte clock gene Per 2 is at its nadir in human biopsy samples. 12 These findings were supported by a similar circadian distribution of left ventricular function, with peak ejection fraction coinciding with the trough of peak creatine kinase release. A similar time of peak infarction (from midnight till 6:00 am) to that of Reiter et al 11 was observed by Fournier et al 13 in a cohort (n=355) of 588 consecutive patients with STEMI from Switzerland.…”
Section: Clinical Observations In Humanssupporting
confidence: 70%
“…By periodic sinusoidal regression analysis, they observed that peak infarct size was 82% greater than trough and occurred at 1:00 am onset of ischemia, a time at which the cardiomyocyte clock gene Per 2 is at its nadir in human biopsy samples. 12 These findings were supported by a similar circadian distribution of left ventricular function, with peak ejection fraction coinciding with the trough of peak creatine kinase release. A similar time of peak infarction (from midnight till 6:00 am) to that of Reiter et al 11 was observed by Fournier et al 13 in a cohort (n=355) of 588 consecutive patients with STEMI from Switzerland.…”
Section: Clinical Observations In Humanssupporting
confidence: 70%
“…25 We noted an increase in aspirin use from 10.8% in the 1992 study by Tofler recent studies have demonstrated that clock genes in human cardiac tissue display significant time-dependent transcriptional variation with peak expression of some clock genes and trough expression of others coinciding with myocardial incidents. 43 Morning hours may also represent nadir levels of some cardioprotective medications. Together, these hemostatic changes, changes in gene expression, and external triggers may create a shearing stress and cause rupture of vulnerable coronary atherosclerotic plaques in the morning, when an elevated prothrombotic state already exists.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of these clocks have been carried out in the fungus Neurospora, in Drosophila and in a variety of rodents, but they have also been found in human cardiac tissue. 4 These peripheral circadian clocks are controlled by so-called "CLOCK" genes that have been found to control approximately 10% of all genes expressed in the mouse heart, which exhibit circadian rhythmicity. 5 This results in cyclic variations in mRNA and protein synthesis and thereby influence cardiac contractile function as well as oxidative and nonoxidative metabolism of carbohydrates and lipids.…”
mentioning
confidence: 99%